2007
DOI: 10.3892/or.17.1.209
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced lung cancer cell killing by the combination of selenium and ionizing radiation

Abstract: Selenium has been associated with anticancer activity by affecting multiple cellular processes. We reasoned that the simultaneous modulation of multiple radioresponse regulators by selenium should increase radiosensitivity if selenium is combined with radiation in cancer therapy. Therefore, we explored the possibility of whether we could obtain an enhancement of radiosensitivity by the combination of selenium and ionizing radiation. We used two human lung cancer cell lines, NCI-H460 and H1299, as well as a hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 21 publications
2
34
0
Order By: Relevance
“…These observations suggest that high levels of MnSOD may protect normal cells against superoxide generated apoptosis by Se. Studies also showed that selenite enhanced cancer cell killing by radiation, suggesting a synergism of prooxidant effects of Se and radiation in cancer cells [38,39]. These data support the notion that prooxidant effects of superoxide and other ROS are responsible for apoptosis induced by certain Se compounds.…”
Section: Discussionsupporting
confidence: 73%
“…These observations suggest that high levels of MnSOD may protect normal cells against superoxide generated apoptosis by Se. Studies also showed that selenite enhanced cancer cell killing by radiation, suggesting a synergism of prooxidant effects of Se and radiation in cancer cells [38,39]. These data support the notion that prooxidant effects of superoxide and other ROS are responsible for apoptosis induced by certain Se compounds.…”
Section: Discussionsupporting
confidence: 73%
“…Nuclear Ku70/ Ku80 proteins were upregulated during gastric cancer cell hyperplasia in a COX-2-dependent manner, and inhibition of Ku80 using COX-2 inhibitors suppressed cell proliferation (Lim et al, 2002). Suppression of Ku80 was also shown to inhibit cell proliferation and induce apoptosis in human colon cancer cells (Li et al, 2002), and downregulation of Ku80 along with other proteins involved in the DNA damage response enhanced the radiosensitivity of lung cancer cells exposed to selenium and ionizing radiation (Shin et al, 2007). Introduction of antisense Ku70 into a human squamous cell lung carcinoma cell lines was also previously shown to increase the radiosensitivity as well as chemosensitivity of these cells (Omori et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics help to explain both the cytotoxic activity of sodium selenite (SSE) alone and its radiosensitizing effect. Sodium selenite has been reported to radiosensitize both hormone-dependent (LAPC-4) and hormone-independent (DU-145) prostate cancer cells (6) and lung cancer cells (9) in vitro. In the experiments described in this report, we studied the in vivo effect of SSE in combination with local tumor irradiation of hormone-independent prostate cancer xenograft tumors.…”
Section: Introductionmentioning
confidence: 99%